DEVELOPING SUFISTIC LEARNING: Considering Pluralistic Consciousness in Islamic Education - Imam Hanafi (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2011)
Differences always create a complex problem. This can be seen by the fact that variety of religions, ethnics, and languages provoked many riots in Indonesia. As a result, these riots made ‘black history’ in this country. Therefore, it is very important to formulate a philosophical framework in order to solve this problem. Education is one of important media to solve this problem. In this case, education has to create an excellent learning methodology that can accept the variety of religions, ethnics, and languages in the classroom. In this article, there is learning methodology, which can be called Sufism model. This methodology develops both intellectual (ratio) and spiritual capability, which connect the esoteric dimensions of human being. This Sufism learning methodology engages the substantial meaning from Sufism tradition in order to translate human’s activity based on spiritual aspects. Therefore, human beings are not framed on symbolic meaning that makes differences become a complex problem.